Propyl 2-(5-bromo-3-methylsulfinyl-1-benzofuran-2-yl)acetate - Choi, Hong Dae (International Union of Crystallography, 2009)
In the title compound, C(14)H(15)BrO(4)S, the S atom has a distorted trigonal–pyramidal coordination. The O atom and the methyl group of the methylsulfinyl substituent lie on opposite sides of the plane of the benzofuran fragment. The molecules form slightly slipped π-stacked inversion-symmetric dimers by intermolecular aromatic π–π interactions, with a centroid-to-centroid distance of 3.695 (4) Å between the benzene rings of neighbouring molecules. The crystal packing is further stabilized by intermolecular C—H⋯π interactions between the methylene H atoms of the propyl group towards the benzene and furan rings of neighbouring molecules, respectively. Additionally, the crystal structure exhibits weak intermolecular C—H⋯O hydrogen bonds.